IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 TENTANG BATAS USIA CALON PRESIDEN DAN WAKIL PRESIDEN TERHADAP DOKTRIN NEGATIVE LEGISLATOR DAN POSITIVE LEGISLATOR - Ogie Nuggraha; Francisca Romana Harjiyatni; Pudja Pramana KA (Fakultas Hukum Universitas Janabadra, 2025)
This research aims to describe and explain the legal considerations of constitutional judges in decision number 90/PUU-XXI/2023 and to outline the implications of decision number 90/PUU-XXI/2023 for the position of the Constitutional Court as a negative legislator. This research uses normative legal research. The research approach uses a statutory approach and a case approach through the Constitutional Court decision Number 90/PUU-XXI/2023. This research is descriptive analytical, namely research that presents careful data about humans and the symptoms of a developing society and these facts are analyzed based on theories or legal principles that correlate with the legal events in question. This research was conducted based on secondary data sources, namely library materials such as official documents, statutory regulations, scientific works, books, articles and other documents/manuscripts related to the object of this research. The results of the research and discussion are related to the concept of open legal policy, which is often questioned by the Constitutional Court in several of its decisions, especially in decision 90/PUU-XXI/2023 which examines the constitutionality of Article 169 letter q of Law Number 7 of 2017 concerning General Elections. There has been a shift if you read carefully the legal considerations (ratio decidendi) of the constitutional judges in the decision. Then the formulation of the age limit was interpreted by the Constitutional Court as an open legal policy due to the technical nature of the procedure which is essentially not within the Constitutional Court's authority to decide.